Effectiveness of cinacalcet treatment for secondary hyperparathyroidism on hospitalization: Results from the MBD-5D study - Asada, Shinji; Yoshida, Kazuki; Fukuma, Shingo; Nomura, Takanobu; Wada, Michihito; Onishi, Yoshihiro; Kurita, Noriaki; Fukagawa, Masafumi; Fukuhara, Shunichi; Akizawa, Tadao (PLOS ONE, 2019)
To elucidate the effect of cinacalcet use on all-cause and cause-specific hospitalization outcomes using a prospective cohort of maintenance hemodialysis patients. We used data from a prospective cohort of Japanese hemodialysis patients with secondary hyperparathyroidism and examined baseline characteristics as well as longitudinal changes. All patients were cinacalcet-naïve at study enrollment. Further, we used a marginal structural model to account for time-varying confounders on cinacalcet initiation and hospitalization outcomes, and an Andersen-Gill-type recurrent event model to account for any recurring events of hospitalization in the outcome analysis using the weighted dataset. Among the 3,276 patients, cinacalcet treatment was initiated in 1,384 patients during the entire follow-up. Cinacalcet users were slightly younger, included more patients with chronic glomerulonephritis and fewer patients with diabetes, were more likely to have a history of parathyroidectomy, and were more often used receiving vitamin D receptor activator, phosphate binders, and iron supplements. The overall hospitalization analysis yielded a hazard ratio (HR) of 0.97 (95% confidence interval [CI]: 0.80, 1.18). A trend toward a mild protective association was observed for cardiovascular-related hospitalizations (HR: 0.85; 95% CI: 0.64, 1.14). In the subgroup analysis, a protective association was seen due to cinacalcet use for infection-related hospitalizations in the lowest intact parathyroid hormone group (HR: 0.36; 95% CI: 0.14, 0.95). Cinacalcet initiation in patients on maintenance hemodialysis had no effect on all-cause and cause-specific hospitalizations. Although the overall association was statistically not significant, cinacalcet may have a protective association on cardiovascular-related hospitalization in all patients and infection-related hospitalization in patient with low intact parathyroid hormone.